The first record of a Longman’s beaked whale (Indopacetus pacificus) newborn neonate found on Miyako Island, Okinawa, Japan - Kobayashi, Nozomi; Ozawa, Sachie; Hanahara, Nozomi; Tokutake, Koji; Kaneshi, Takaaki; Inoue, Ken; Okabe, Haruna; Miyamoto, Kei; Ueda, Keiichi (Marine Biodiversity Records, 2021)
The Longman’s beaked whale ( Indopacetus pacificus ) is one of the rarest cetaceans worldwide. Since it was first described as its own species in 1926, they have been observed alive at sea on several occasions, and less than 20 strandings have been reported worldwide to date. Thus, basic information regarding this species, such as the maximum size of adult individuals or body length at birth, remains unknown. In this study, the external appearance and DNA analysis of a female Longman’s beaked whale stranded on Miyako Island, Okinawa, Japan, are reported. The external appearance of the specimen matched the features of the Longman’s beaked whale presented in previous studies. The mitochondrial DNA control-region sequences obtained from the specimen also matched the reference sequences of the species deposited in GenBank. Based on these features, the specimen was confirmed as a Longman’s beaked whale. The specimen was estimated to be neonate because of its body length (235 cm) and the clear several fetal folds observed on its body surface. To the best of our knowledge, this is the first report of a confirmed new born neonate of Longman’s beaked whale in the world.